Multikulturalisme dalam Mal - Dionius Bismoko Mahamboro; Sem Porak Tangkeliku; Salvinus Salamba (Jurnal Orientasi Baru, 2007)
Local identity has been considered as one legitimate concern in the rise of the culture of globalization. The establishing of malls in the city of Yogyakarta which is well-known as 'the city of culture' has provoked discourse about local identity since malls are often considered as a symbol of globalization. Some say that traditional market, one of the icons of the city, will not be able to compete with the modern one, and it could be marginalized and eventually eliminated by the global market. But, malls should not merely be regarded as menace for local identity especially if it is seen as a 'cultural moment'. Malls could become a place of encounter among local cultural products as well as with global elements which might result an empowering multiculturalism.